Work stress, employee capacity, and organizational policy: A quantitative study on the effects of age and job rotation on work ability - Zahroh, Desi Apriliana; Utari, Dyah (Asian Journal of Toxicology, Environmental, and Occupational Health, 2025)
Background: Employability is the capacity possessed by every worker and is a balanced value between personal resources and work factors. Methods: This study used a cross-sectional study design with a research sample of 99 respondents obtained through simple random sampling technique. This research instrument uses The Workplace Stress Scale to measure work stress and the Work Ability Index to measure work ability. This study used chi-square test analysis and multiple logistic regression. Findings: Work ability can be affected by work stress because it disrupts individual health and has an impact on the company. This study aims to determine the relationship between work stress levels and work ability in employees of Company P in 2024. Conclusion: The results showed that the level of work stress was significantly associated with work ability (p=0.003; POR=4.209; 95% CI=1,708-10,369). The results of multivariate analysis showed that age (p=0.017; POR=0.222; 95% CI =0.065-0.761) and job rotation (p=0.000; POR=76.951; 95% CI=12.524-472.811) were confounding variables of the relationship between work stress level and work ability. Novelty/Originality of this article: In this study, the variable most related to work ability is job rotation. Companies can consider before rotating employees and facilitating training in specialized fields so that employees have skills in related fields.